Heat Dissipation Enhancement Using Graphene Heat Sink - Wong, Jer Jian (Universiti Sains Malaysia, 2021)
Heat dissipation is one of the challenges that need to be tackled to enhance the performance of the electronic components. In current study, the numerical investigation on the use of graphene in designing a plate fin heat sink and evaluation of thermal performance by comparing with the conventional material (copper and aluminium alloy) are performed. In particular, the effects of fin height, heat flux and flow rate of the working fluid on the thermal performance of the heat sink are studied and documented in the thesis. The thermal performance is evaluated in terms of the thermal resistance, average Nusselt number, pumping power required and fin efficiency of the heat sink. This study has shown that the graphene heat sink which has a higher thermal conductivity yields the lowest thermal resistance and gives the highest average Nusselt number among other materials. The pumping power required for the flow of working fluid is independent to the material used. With its high intrinsic thermal conductivity, graphene heat sink reduced the drop in terms of fin efficiency when fin height is increased, the percentage of the fin efficiency drop with the height is not more than 2% in the study.